Mangain Anak Dalam Budaya Batak dan Pembentukan Identitas Religius Remaja HKBP - Roy Martin Sianipar (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This study aims to examine the practice of mangain anak as an inculturative space between Batak culture and Christian faith and to analyze its influence on the formation of adolescents’ religious identity in the HKBP Church. The research employs a qualitative approach with descriptive-analytical methods through interviews, observations, and literature review. The research participants include adolescents in the HKBP Church who have been adopted through mangain, pastors, and Christian Religious Education teachers. The findings indicate that mangain anak has strong theological resonance with the biblical concept of divine adoption, particularly regarding themes of acceptance, new identity, and belonging to the family of God. Nevertheless, the limited implementation of inculturative approaches in Christian Religious Education has prevented the pedagogical potential of mangain from being fully utilized in adolescent faith formation. Therefore, this study emphasizes the importance of developing an inculturative, contextual, and pastoral approach to Christian Religious Education that enables adolescents to integrate their cultural identity and Christian faith holistically within the life of the HKBP Church.